Impact of Goods and Services Tax (GST) on the Hotel Industry (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
The implementation of Goods and Services Tax (GST) has been one of the most significant tax reforms in India, aiming to simplify and unify the country’s tax structure. This research paper examines the impact of GST on the hotel industry, analyzing changes in pricing, customer behavior, and the overall financial performance of hotels. Additionally, the study includes an empirical analysis of data from hotels in a specific region, utilizing a t-test to compare pre- and post-GST revenue performance.